“It is a Dancing and Frivolous Age”: 1920s Youth Culture at Queen’s University - Warner, Anne (Ontario History)

(untitled) (The Ontario Historical Society, 2009)
In the 1920s a distinct youth culture formed in Canada. A key to this culture was the emergence of a modern woman. Her clothing, views on sexuality, and autonomous attitude led many to believe that traditional gender norms were being dismantled. As a co-educational university, Queen’s University of Kingston, Ontario, was an incubator for youth culture. This paper uses Queen’s as a case study to explore the tension between traditional ideals of middle class Canadian society and the values that began to emerge among middle class youth in the 1920s, including those surrounding the emergent modern woman.